2015
DOI: 10.1016/j.cell.2015.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analyses of Human Reprogramming Reveal Dynamic Nature of Induced Pluripotency

Abstract: Summary Induced pluripotency is a promising avenue for disease modeling and therapy, but the molecular principles underlying this process, particularly in human cells, remain poorly understood due to donor-to-donor variability and intercellular heterogeneity. Here we constructed and characterized a clonal, inducible human reprogramming system that provides a reliable source of cells at any stage of the process. This system enabled integrative transcriptional and epigenomic analysis across the human reprogrammi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
284
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 209 publications
(325 citation statements)
references
References 48 publications
(68 reference statements)
17
284
2
5
Order By: Relevance
“…However, inhibition of H3K27 methylases (PRC1/2) limits pluripotency in some studies [119,121], but enhances pluripotency in others [122], suggesting context-dependent functions for H3K27 methylation during reprogramming. It was recently demonstrated that H3K27 methylation is only required at a core set of lineage-specific developmentally regulated genes [123] and loss of H3K27 methylation at these sites greatly diminishes reprogramming efficiency [123].…”
Section: Lessons Learned From Histone Post Translational Modificationmentioning
confidence: 99%
“…However, inhibition of H3K27 methylases (PRC1/2) limits pluripotency in some studies [119,121], but enhances pluripotency in others [122], suggesting context-dependent functions for H3K27 methylation during reprogramming. It was recently demonstrated that H3K27 methylation is only required at a core set of lineage-specific developmentally regulated genes [123] and loss of H3K27 methylation at these sites greatly diminishes reprogramming efficiency [123].…”
Section: Lessons Learned From Histone Post Translational Modificationmentioning
confidence: 99%
“…A recently generated secondary system for human reprogramming has been reported where differentiation of iPS colonies into fibroblasts created lines with clonal integrations of inducible reprogramming factors and constitutive hTERT to overcome senescence and the ability to expand clones. As with other systems, this secondary system generates human iPS cells that are generally very similar to ES cells in their gene expression profiles and histone modifications [15].…”
Section: Bioinformatic Analysis Of Induced Pluripotencymentioning
confidence: 99%
“…Generally, there is agreement that iPS reprogramming generates cells that are very similar to ES cells [15,31,55,61,74]; however, genomic-scale bioinformatics has been able to identify subtle differences between ES and iPS cells. An early meta-analysis of expressional profiling identified a subset of genes and miRs that can differentiate human iPS and ES cells [18].…”
Section: Bioinformatic Analysis Of Induced Pluripotencymentioning
confidence: 99%
See 2 more Smart Citations